Predictors of Willingness to Receive COVID-19 Vaccine: Cross-Sectional Study of Palestinian Dental Students - Kateeb, Elham; Danadneh, Mayar; Pokorná, Andrea; Klugarová, Jitka; Abdulqader, Huthaifa; Klugar, Miloslav; Riad, Abanoub (Vaccines, 2021)
The overarching aim of this study was to assess the predictors related to the willingness of Palestinian dental students to receive the COVID-19 vaccine when it becomes available. A cross-sectional study was conducted among a universal sample of dental students in the Palestinian territories. Willingness to get the COVID-19 vaccine was related to the following factors: Demographic characteristics, COVID-19-related experiences, beliefs and knowledge about the vaccine, attitudes toward vaccinations in general, and other factors outlined by the WHO SAGE Vaccination Hesitancy Questionnaire. Four hundred and seventeen students completed the questionnaire (response rate = 41.7%). In general, 57.8% (n = 241) were willing to take the COVID-19 vaccine when it became available to them, 27% (n = 114) were hesitant, and 14.9% (n = 62) were not willing to get vaccinated. The final regression model explained 46% of the variation in the willingness to receive the COVID-19 vaccine as follows: Attitudes towards new vaccines (β = 6.23, p < 0.001), believing in a favorable risk-benefit ratio (β = 5.64, p < 0.001), trust in the pharmaceutical industry (β = 5.92, p = 0.001), believing that natural immunity is better than being vaccinated (β = -4.24, p < 0.001), and having enough information about the vaccine (β = 4.12, p < 0.001). Adequate information about vaccines, their risk-benefit ratios, and natural and acquired immunity are important to build trust and favorable attitudes towards vaccines among future dentists.
Keywords: cross-sectional studies; dental; social determinants of health; COVID-19 vaccines; mass vaccination; education; students; decision making